Efektivitas Penerapan Metode Shalat Tahajud terhadap Peningkatan Daya Ingat Santri Tahfidz Putri Tingkat I Al-Karimiyah - Nur Ummi Fatayati; Kholifatus Sa'diyah (Kariman: Jurnal Pendidikan Keislaman, 2023)
This study was aimed to increase memory with tahajjud prayers. Method of this study used quasi experiment with one group pre-test and post-test design. The Subject in this study are 11 student in Tahfidzul Quran Boarding school with having same memory abilities and menstrual schedule. This study used an analysis method with observation comparing the result of the pre-test and post-test design. The three result of the alphabetical series , word series, and number series test result, post -test result show a higer value than the pretest value. According to the result of study, it can be said that there was significant that tahajjud prayer scan be increasing the memory of student in Tahfidzul Quran boarding school.